The Civil War letters of Joseph Hopkins Twichell : a chaplain's story - Twichell, Joseph Hopkins, 1838-1918 (University of Georgia Press, 2006)
"In 1861 young Joseph Twichell cut short his seminary studies to become a Union Army chaplain in New York's Excelsior Brigade. A middle-class New England Protestant, Twichell served for three years in a regiment manned mostly by poor Irish American Catholics. This selection of Twichell's letters to his Connecticut family will rank him alongside the Civil War's most literate and insightful firsthand chroniclers of life on the road, in battle, and in camp. As a noncombatant, he observed and participated in the momentous events of the Peninsula and Wilderness Campaigns as well as the battles of Second Bull Run, Fredericksburg, Chancellorsville, Gettysburg, and Spotsylvania."